The Effect of Accounting Information Systems and Internal Control Systems on The Quality of Financial Statements at BPKAD - Kania Kania; Abdul Hafiz Tanjung (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
The Effect of Accounting Information Systems and Internal Control Systems on the Quality of Financial Statements at BPKAD Bandung The dependent variable in this study is the Quality of Financial Statements. This study uses a sample through the process of dividing the population into strata or what is called stratified random sampling. The data in this study are primary data obtained from distributing questionnaires directly to employees who are directly involved in making financial reports. The results of the study partially show the information system and internal control system have an effect on the quality of the report.